INVESTIGATION ON CONVERSION EFFICIENCIES OF MULBERRY LEAVES IN SILKWORM Bombyx mori L. DURING THE PROGRESS OF ENTOMO-PATHOGENIC FUNGUS Beauveria bassiana (Bal) Vuill. - BEGUM, SYEDA FAKRUNNISA; SAVITHRI, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Silkworm Bombyx mori is an economically important monophagous insect which is thoroughly domesticated by providing all the requisites for its growth and survival. Due to domestication over centuries, silkworms have become very gentle and delicate to the environmental conditions and different types of micro-pathological agents. The microorganisms such as virus, bacteria, fungi and protozoa cause diseases such as grasserie, flacherie, muscardine and pebrine which are the major threat to the sericulture industry. Chandrasekaran and Nataraju [1] stated that, out of the total crop loss due to different diseases, 10 to 40 per cent of crop loss occurs due to fungi, Beauveria bassiana in India. Nutrition is the basic unit of silkworm growth and development. Feeding and conversion efficiency of mulberry leaves such as leaf to cocoon ratio, leaf to shell ratio etc., in silkworm is one of the commercially important factors to obtain good dividends. Silkworm acquires its essential nutrients and water from the mulberry leaves it consumes. Various nutritional parameters such as ingestion of mulberry leaf, digestion, Efficiency of Conversion of Ingesta to Larva, Efficiency of Conversion of Digesta to Larva, Efficiency of Conversion of Ingesta to Cocoon, Efficiency of Conversion of Digesta to Cocoon, Efficiency of Conversion of Ingesta to Shell, Efficiency of Conversion of Digesta to Shell, I/g- Cocoon, D/g- Cocoon, I/g-Shell, D/g-Shell were estimated in the present investigation in Beauveria bassiana infected silkworms compared to untreated silkworms to understand the conversion efficiencies in infected silkworms. The results indicated a drop in ingesta, digesta, conversion efficiencies of ingesta and digesta to larva, cocoon and shell in the inoculated silkworms. On the contrary, ingesta and digesta required to produce one gram cocoon and one gram shell was higher in inoculated silkworms than in healthy silkworms. So, there is need to understand the various mechanisms involved and physiological changes occurring in the silkworm due to diseases which may be useful in developing prophylactic measures to overcome the attack of diseases.